NEGOTIATING ISLAMIC AUTHORITY: TRANSNATIONAL MOVEMENTS AND RELIGIOUS CONTESTATIONS IN YORUBALAND, NIGERIA - Nafiu Ahmed Arikewuyo (UIN Walisongo Semarang, 2025)
The modern Islamic thoughts are essentially influenced by transnational Islamic movements with their diverse inclinations. Such an influence wielded by these movements differs from one location to another. Against this backdrop, this paper studies the influence on Muslims in Yorubaland of Nigeria, with specific focus on religious polemics introduced by the advent of these movements in the region under study. Descriptive method of research was adopted. The study shows that though there are different transnational movements in Yorubaland, the most controversial and popular in contemporary time are the Muslim Brotherhood and Salafiyyah groups. The religious polemics evoked by the advent of the transnational Islamic movements in the region under study include the religious controversy between the traditional Muslims and adherents of these movements as well as the polemics that exist among the various movements against one another. The study recommends display of high level of ethics of disagreements among the traditional and the revivalist Muslims in Yorubaland as well as statutory regulation of religious practice by the concerned authorities in order to forestall the turning of religious polemics to physical crisis in the region.